The book of inventions - Harrison, Ian, 1965- (Washington, DC : National Geographic, 2004)
Relates the histories of over 120 inventions that have become staples of modern life, including the electric iron, sliced bread, the wine box, submarines, typewriters, jet skis, the disposable syringe, and bar codes, each with photographs, facts, and anecdotes.
Cover title: National Geographic the book of inventions.
Includes bibliographical references (p. 287) and index.
Young Adult
Young Adult
Wilson's Senior High School
Booklist
Keywords: Inventions -- History; Inventors -- Biography; Inventions -- History; Inventors -- Biography